Single and Multiple Dose Pharmacokinetic Evaluation of a Transdermal Delivery System of Imipramine Hydrochloride - Panchagnula, Ramesh; Dravid, Prajakta; Jain, Amit; Khandavilli, Sateesh (Arzneimittelforschung, 2005)
The transdermal route provides an attractive alternative to the presently used peroral therapy with tricyclic antidepressants due to the avoidance of first-pass metabolism and the associated side effects. In this investigation an earlier developed transdermal delivery system (TDS) of imipramine hydrochloride (CAS 113-52-0; IMH) was evaluated with respect to dose proportionality at three different dose levels. Linearity was observed with the lower doses. For the prediction of in vivo plasma levels, various pharmacokinetic parameters such as a, ß, volume of distribution, and AUC0→ were determined by single dose intravenous administration (2 mg/kg). The lowest dose was selected for the multiple dose study taking into consideration the issues of stability, safety, therapeutic range and linearity of pharmacokinetics. At all dose levels the experimental plasma values were significantly lower than predicted levels (p < 0.05) but 30–50 fold higher than the therapeutic range with no significant difference at different dose levels. The plasma levels obtained by repeated application were comparable to that obtained in the single dose study. In addition, IMH exhibited dose proportional pharmacokinetics at the higher doses (above 50 mg/day). The developed TDS was able to maintain steady-state plasma levels for the entire duration of the multiple dose study.
Keywords: Antidepressant, tricyclic; CAS 113-52-0; Imipramine hydrochloride, dose proportionality, multiple dose, pharmacokinetics; transdermal delivery system